KUALITAS PELAYANAN PUBLIK APARATUR SIPIL NEGARA DI KANTOR KECAMATAN WORI KABUPATEN MINAHASA UTARA - Randang, Julius; Lumolos, Johny (JURNAL ILMIAH SOCIETY, 2016)
This study aims to assess the quality of public services with the State Civil Apparatus, using qualitative research method. Research shows that the role of government officials in relation to the public service in general can be quite adequate it is seen from the role of government officials in the performance of duties and responsibilities, system services provided, procedures and working methods of service, the ability to provide services, the behavior of officials in providing services as well as standard service charge required in general is quite good. Keywords: Quality, Service Delivery.